COMPLIMENT RESPONSE STRATEGIES AMONG STUDENTS AT UNIVERSITY OF BALIKPAPAN - Retnowaty, Retnowaty (STKIP Muhammadiyah Pringsewu, 2018)
When someone gives a compliment, the hearer should response it to smoothen the relationship and communication. This study attempts to explore how the University of Balikpapan Students respond to compliment. This was a qualitative study. The data in this study were collected using a discourse completion task (DCT) to elicit compliment responses from students in University of Balikpapan as the participants. Moreover, the data were analyzed with the Continua of Compliment Response Strategies proposed by Tran (2007). It was found that most participants used variation of compliment response strategies. However, they tended to use the acceptance to denial continuum responses.